Pola Distribusi Siput Air (Gastropoda) sebagai Bioindikator Pencemaran Air di Sungai Unus Kota Mataram dalam Upaya Pengembangan Modul Ekologi - Sofiana, Laily; Nofisulastri, Nofisulastri; Safnowandi, Safnowandi (Biocaster : Jurnal Kajian Biologi, 2023)
The results of preliminary observations on the Unus River in Mataram City show that the gastropods in each village which the river flows through have different characters according to the activities around the river and the level of river water pollution. Pollution and the high activity of residents who use the river as a residential area, indications of pollution in the Unus River can be seen from the condition of the river estuary which is quite dirty, so great ecological pressure is occurring in the river, it is necessary to conduct research on the community structure of macrozoobenthos, especially water snails as a bioindicator of water quality in the Unus River, Mataram City in an effort to develop an ecological module. The aims of this study were: 1) to find out how the pattern of distribution of gastropods in the Unus River, Mataram City; 2) identify the types of gastropods found in the Unus River, Mataram City; 3) reveal the population of Gastropod dominance that dominates the Unus River in Mataram City; 4) analyze the population density of Gastropods in the Unus River, Mataram City; 5) analyzing the diversity of gastropod species in the Unus River, Mataram City; and 6) developing research results on distribution patterns of gastropods as bioindicators of water pollution in the Unus River, Mataram City in an effort to develop an ecological module. This type of research is descriptive exploratory and developmental research for the development of ecological modules. The sampling technique used was purposive sampling technique and the length of the transect used was 30 m. Based on the results of the study, the highest morbidity index was the Thiara requenti species with a value of 0.253 which was in the regular category. Found 12 species from 5 families namely; Pomacea canaliculata, Mellanoides plicaria, Apella demisum, Mellanoides puncata, Taribea granifera, Goniobasis virginica, Fillopaludina javanica, Thiara scabra, Thiara sp, Thiara requenti, and Mellanoides tuberculata. The highest Gastropod dominance population was owned by the Mellanoides plicaria species with a total of 0.48. The highest population density is occupied by the species Thiara requenti with a value of 7.3. The highest level of Gastropod diversity is located at station 2 with a value of 1.82. Based on the results of the validation and readability test of the ecological module, an average value of 90 and 82.9 was obtained for the legibility test, so it can be concluded that the module is very feasible to use.